Perbandingan Hasil Uji Performans Calon Induk (Heifer) Sapi Aceh dengan Metode Indeks Seleksi (IS) dan Nilai Pemuliaan (NP) - W P B. Putra; Su madi; T. Hartatik; H. Saumar (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
This research was conducted to investigate the results of selection in Aceh cattle candidatebull using breeding value (BV) and selection index (SI) methods. The Secondary data in this research was records data from 2010 to 2013 and consisted of family tree, birth and body weight records at Indrapuri’s Breeding and Forages Centre (IBFC) of Aceh Cattle. Data records collected for estimate heritability nor the genetic and phenotypic correlations. The research showed that heritability value of weaning weight (WW), yearling weight (YW) and final weight (FW) included high category. Genetic correlation between WW with YW and FW were positively moderate. The concluded of this research was 48 % heifers had same rank on BVFW and SI from 29 heifers. Index selection method could be use for livestock selection criteria.Key words: Aceh cattle, breeding value, selection index, heritability, genetic correlations